2014
DOI: 10.1634/theoncologist.2013-0427
|View full text |Cite
|
Sign up to set email alerts
|

Discordance in Hormone Receptor Status Among Primary, Metastatic, and Second Primary Breast Cancers: Biological Difference or Misclassification?

Abstract: Introduction. Discordance in hormone receptor status has been observed between two breast tumors of the same patients; however, the degree of heterogeneity is debatable with regard to whether it reflects true biological difference or the limited accuracy of receptor assays. Methods. A Bayesian misclassification correction method was applied to data on hormone receptor status of two primary breast cancers from the Surveillance, Epidemiology, and End Results database between 1990 and 2010 and to data on primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 58 publications
0
34
0
Order By: Relevance
“…18 It is a strength of our study that, being a single-institution study, the pathologic assessment was consistent for our patients.…”
Section: Discussionmentioning
confidence: 58%
“…18 It is a strength of our study that, being a single-institution study, the pathologic assessment was consistent for our patients.…”
Section: Discussionmentioning
confidence: 58%
“…Let H i , i = 1,2 denote the true HR status (1 for positive and 0 for negative) and Hi denote the observed HR status for the i ‐th cancer. There are 1603 distinct values of ()X1,X2,X3,H1, which is a finer stratification than that used in where X 3 is dichotomized. It is worth noting that the method proposed in this paper differs from the method developed in in two aspects.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…There are 1603 distinct values of ()X1,X2,X3,H1, which is a finer stratification than that used in where X 3 is dichotomized. It is worth noting that the method proposed in this paper differs from the method developed in in two aspects. First, the model for continuous X 3 is in a different parametric form to account for the curved relationship.…”
Section: Proposed Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although loss of ER expression would appear to be a reasonable explanation for the emergence of endocrine resistance, studies of paired primary and metastatic tumor samples indicate that this occurs in only 10% of cases (Sighoko et al 2014). Similarly, Ellis et al (2008) found loss of ER expression during neoadjuvant endocrine therapy in less than 10% of patients, and notably in fewer than 20% of non-responders, who would be expected to represent an endocrine-resistant phenotype.…”
Section: Mechanisms Of Resistance: Esr1 Mutationsmentioning
confidence: 99%